Perbedaan Kemampuan Menulis Karya Ilmiah Mahasiswa PGSD UM Palangkaraya Ditinjau dari Pemberian Resitasi dan Jenis Kelamin - Bulkani Bulkani (Anterior Jurnal, 2014)
This study aimed to identify (1) writing ability differences between students which given recitation in writing research proposal and analyzing thesis, compared with recitation only in writing research sproposal, (2) writing paper ability differences between male students and female students, (3) writing paper ability differences based on the recitation and gender. while sample taken from 2 classes and treated as experiment class I and II. In experiment class I students were given assignment to write research proposal and then analyzed thesis which had been tested. In experiment class II students were only writing the proposal. The instrument were pretest and posttest in essay. And to analyze the data used t test, ANOVA one way and two way by using SPSS program. Based on the result can be concluded that : (1) students writing ability who given recitation in writing proposal and analyzed the thesis are better than students who given recitation and writing proposal only with F count = 11,987 which significant at level 1% (2) female students have better writing ability than male students, with Fcount = 6,623 significant level 5% (3) female group which given recitation to write proposal and analyze thesis is the highest group in writing paper ability, then the male group which given the recitation to write and analyze thesis, the female group which given recitation only in writing proposal and the last is female group which given recitation only in writing proposal. Score F count between factors F = 6,467 significant at level 1%.